Access to Justice and Human Rights Protection in the Common Law Jurisdiction in Cameroon: Problems and Prospects (Texas Journal of Multidisciplinary Studies, 2021)
The article examines the importance of access to justice as an essential instrument for the protection of human rights in Cameroon. It demonstrates that the fundamental rights of persons are best protected and enforced through the process of access to the court. The article further unravels the reality of the Cameroonian situation and posits that there are several obstacles to the realization of access to justice in the country. These obstacles, such as undue delay in the administration of justice, high cost of litigation, reliance on technical rules, locus standi, and illiteracy, are examined in turn, in validation of the proposition. Finally, it inquires on the prospects for improvement of access to justice in Cameroon by advocating for judicial reforms, the resort to alternative dispute resolution mechanisms, less reliance on technical legal rules, and the availability of legal aid schemes as decisive measures liable to positively impact on the quest for the protection of human rights in the country